STUDENT SERVICES INFORMATION SYSTEM IMPLEMENTATION CASE STUDY: THE STUDY PLAN CARD ON-LINE IN JAKARTA STMIK STI&K - Irfan IF Irfan (Majalah SIKOMTEK, 2010)
The success of a college that can not be separated from palayanan given to students in particular about the manner of taking courses that will be given in each semester. KRS- making system on line this will greatly help the student in completing his studies and to facilitate in determining the number of active students.